2003
DOI: 10.1007/s10350-004-6626-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Analysis in Patients With Fournier's Gangrene

Abstract: The interval from the onset of clinical symptoms to the initial surgical intervention seems to be the most important prognostic factor with a significant impact on outcome. Given the significantly high mortality rate among diabetics, diabetes is also an independent prognostic factor. Despite the decreased number of idiopathic cases and extensive therapeutic efforts, Fournier's gangrene remains a surgical emergency, and early recognition with prompt radical debridement is the mainstays of management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
2
18

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(160 citation statements)
references
References 14 publications
5
135
2
18
Order By: Relevance
“…As a result, skin gangrene occurs at the areas vascularized by these blood vessels. The isolated bacteria in Fournier's gangrene further propagate the endarteritis, which was formed by endotoxins, through platelet aggregation and complement fixation by production of coagulase, hyaluronidase, collagenase and heparinase (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, skin gangrene occurs at the areas vascularized by these blood vessels. The isolated bacteria in Fournier's gangrene further propagate the endarteritis, which was formed by endotoxins, through platelet aggregation and complement fixation by production of coagulase, hyaluronidase, collagenase and heparinase (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…(5) In our case series, patient present between the 3-8 days after the onset of disease .Late presentation in surgical OPD may be because of social stigma or lack of awareness However in our study no any mortality was reported. We have performed aggressive surgical debridement and proper coverage of broad spectrum antibiotics.…”
Section: Discussionmentioning
confidence: 48%
“…2,3,8,10,26 No trato digestório foram relatados focos originários em abscessos perianais, carcinomas do cólon e do reto, apendicites e diverticulites agudas, Doença de Crohn, hérnias encarceradas, e perfuração do reto por corpo estranho (osso de frango). 11,19,25,27 Em artigo de revisão, abrangendo 1726 casos, as afecções cutâneas lideram a sede dos focos de infecção respondendo por 24 % dos casos.…”
Section: -Etiologiaunclassified
“…19 Independente da substância aplicada, a experiência mostra que o principal aspecto relevante no curativo é a limpeza mecânica com soro fisiológico e até com água e sabão neutro.…”
Section: -Fatores Prognósticosunclassified